2013
DOI: 10.3390/md11051506
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Bioactivity Present in a Unique Marine Bacteria Collection from Portuguese Deep Sea Hydrothermal Vents

Abstract: Interesting biological activities have been found for numerous marine compounds. In fact, screening of phylogenetically diverse marine microorganisms from extreme environments revealed to be a rational approach for the discovery of novel molecules with relevant bioactivities for industries such as pharmaceutical and cosmeceutical. Nevertheless, marine sources deliverables are still far from the expectations and new extreme sources of microbes should be explored. In this work, a marine prokaryotic collection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…These chemicals show potential for having pharmaceutical properties and applications, including antibiotics (Liu et al, 2013) and anticancer compounds . Albeit surprising coming from a habitat with no light, even photoprotectives for potential use in sunscreens and cosmetics have been found in deep-sea hydrothermal vent habitats (Martins et al, 2013). While less than 2 % of the marine natural products being explored come from the deep sea (Skropeta, 2013), the potential of novel molecules and genetic pathways within this habitat is vast.…”
Section: Bioprospectingmentioning
confidence: 99%
See 1 more Smart Citation
“…These chemicals show potential for having pharmaceutical properties and applications, including antibiotics (Liu et al, 2013) and anticancer compounds . Albeit surprising coming from a habitat with no light, even photoprotectives for potential use in sunscreens and cosmetics have been found in deep-sea hydrothermal vent habitats (Martins et al, 2013). While less than 2 % of the marine natural products being explored come from the deep sea (Skropeta, 2013), the potential of novel molecules and genetic pathways within this habitat is vast.…”
Section: Bioprospectingmentioning
confidence: 99%
“…The deep ocean is the source of a number of novel natural products isolated from the highly diverse and species-rich deep-sea faunal communities (Skropeta, 2008), in particular from those found at hydrothermal vents (Thornburg et al, 2010;Martins et al 2013). As of 2008, 78 natural products have been isolated from as many as 19 classes and from all Domains of life (Skropeta, 2008).…”
Section: Bioprospectingmentioning
confidence: 99%
“…Alteromonas, Halomona, Vibrio, Acinetobacter, Shewanella, Pseudomonas, and Rheinheimera, of the Gammaproteobacteria phylum were also isolated from both HV1 and HV2. Of these 7 genera, the first 6 have been detected in hydrothermal fields around the world (Kaye et al 2011;Martins et al 2013;Pena et al 2012;Raguenes et al 2003;Rajasabapathy et al 2014), while the last one was identified in vent environments for the first time. The roles of these bacteria in hydrothermal vent ecosystems remain to be elucidated.…”
Section: Isolates That Exhibited Two Types Of Extracellular Activitymentioning
confidence: 96%
“…Resources in the deep sea are increasingly being exploited by bioprospecting, or the search for natural products within biological resources. The deep ocean is the source of a number of novel natural products isolated from the highly diverse and species-rich deep-sea faunal communities (Skropeta, 2008), in particular from those found at hydrothermal vents (Thornburg et al, 2010;Martins et al 2013). As of 2008, 78 natural products have been isolated from as many as 19 classes and from all Domains of life (Skropeta, 2008).…”
Section: Bioprospectingmentioning
confidence: 99%